Re-wired - Fan, Jason Yuk Hei (2019)
This report presents RE-WIRED, a Wee Kim Wee School of Communication and Information (WKWSCI) undergraduate Final Year Project campaign to encourage Singaporean youth aged 18 to 25 to reduce their electrical and electronic waste (e-waste). Organised by four final year students from WKWSCI, Nanyang Technological University, the campaign spreads awareness about five e-waste reducing behaviours: donating, recycling, repairing, reselling and trading in.